Pemujaan Arca Lembu Nandini Di Ashram Lembah Bhayam (Perspektif Pendidikan Agama Hindu) - Komang Ayu Yenny Trisna Dewi; I Ketut Sudarsana; I Made Dian Saputra (Jayapangus Press, 2019)
This study aims to determine the implementation, function and meaning, as well as the values ​​of Hindu religious education contained in the worship of Nandini Arca Cattle in the Bhayam Valley Ashram in Babahan Village, Babahan Village, Tabanan Regency. Data collection in this study uses several methods, namely: interview observation, documentation study and literature study. The collected data was analyzed by qualitative descriptive analysis method with steps to reduce, present data, and draw conclusions. The results of this research are (1) the implementation of the Nandini Ox Statue worship in Bhayam Valley Ashram is carried out in 3 stages, namely the planning stage, the core stage, and the closing stage. (2) Functions and Meanings of the worship of the Nandini Ox statue in the Bhayam Valley Ashram include; 1) Function of Religion, 2) Social Function, 3) Function of Cultural Conservation and 1) Meaning of Welfare, 2) Meaning of Solidarity. (3) Hindu Educational Values ​​in the worship of the Nandini Ox Statue, namely; 1) Educational Value of Sradha Bhakti, 2) Value of Ethical Education, 3) Value of Aesthetic Education, 3) Value of Aesthetic Education.